Religion, rebellion and class consciousness in the tin mining communities in Bolivia - Nash, June (1985)
In the competition to win the souls of the American Indians, missionaries, spiritual leaders of the pre-conquest society, viceroys, governors and popular leaders have tried for 400 years to create a sense of dissent between what they propose and other ideological of the world. This has been a means of promoting and maintaining their exclusive authority and leadership. The mining towns of the altiplano have resisted this attack on their beliefs (Nash, 1979). The mining families understand a superhuman world of saints, devils, gods and enchanted beings with whom they live in the mine, the camp and the region. They tend to dismiss ideologies that are very contradictory to what they have felt in their unique world view.